PERANCANGAN VIDEO PROMOSI RCM DJ SCHOOL DI KOTA PADANG - Alvino Atintri; m.nasrul kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The purpose of this design is to design effective and efficient promotional media to introduce potential customers so that they get the services they sell. One of them is the audio visual media, which is very much an audio visual media seen in the current era.The analytical method used is 5W + 2H (what, who, where, when, why, how and how much) to find solutions to the problems encountered.This design produces an audio visual in the form of a promotional video that can display images and sound as the main media, and is also supported by several other media, namely: Poster, T-Shirt, Billboard, Totebag, Sticker, X-Banner as supporting the main media and as a promotional media.Keywords: DJ, RCM DJ SCHOOL, Promotion